RESEARCH PROGRESS OF METHODS OF GEAR FAULT DIAGNOSIS - ZHAO LiJuan; LIU XiaoDong; LI Miao (Jixie qiangdu)
Gear is a main component of the machinery transmission. Reducing gear failure and prolong its life is a crucial issue in industrial production. It summarized the research progress of gear fault diagnosis technology for nearly 50 years. The gear fault diagnosis methods are classified,mainly including the time domain method,frequency domain method,time-frequency domain method,the intelligent diagnosis method and oil detection. This paper elaborates their application example in the gear failure and analysis the characteristics and application example of gear fault diagnosis technology. It expounds several kinds of typical fault diagnosis technology and signal processing method in the modern application of gear fault diagnosis. Comprehensively reviewed the research status of signal measurement technology and the development. It summarized characteristics of modern gear fault diagnosis technology and pointed out the gear fault diagnosis technology in detail later. It will towards to the development of intelligent,diversification,efficient direction and provides the basic basis for the fault diagnosis of the gear system and test under the running state,to ensure the safe operation of the gear. The study of gear fault diagnosis technology has a certain significance.